Meckel’s Diverticulitis and Reactive Appendicitis in an Adult Woman: Clinical Case - Figueroa-Araujo, Demian; Flores-López, Alejandro Alberto; Cano-García, Maria Ximena; Viniegra, Itzel Velázquez; Flores-Reyes, Marco Faryd; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Introduction: Meckel’s diverticulum (MD) remaining from the yolk duct is the most common congenital anomaly of the gastrointestinal tract, with a prevalence of 2 percent in the general population. Most MDs are asymptomatic and usually discovered incidentally by imaging studies or during abdominal surgery. In countries with poor distribution of wealth, there is a rate of 4 to 6%. Age-related differences in presentation are observed, ranging from incidental findings to intestinal obstruction, bleeding, and inflammation. The difference between children and adults is that in the former, it presents as a hemorrhage, and in the latter, an obstruction. Clinical Case: A 54-year-old female was admitted to the emergency department due to abdominal pain with a history of previous abdominal surgery; she began suffering 24 hours ago with stabbing abdominal pain, located in the epigastrium and mesogastrium, of intensity 9/10 and radiating to the right iliac fossa; hyporexia, nausea, and vomiting of gastrobiliar content. She presented pain on palpation in the right iliac fossa and with decreased peristalsis; positive Blumberg, Rovsing, and MacBurny signs and identified a post-incisional wall defect. Exploratory laparotomy was done, and the etiology of the obstructive process was discovered. Discussion: Since Meckel’s diverticulum is rarely in adults, there is no consensus on what type of procedure to perform for symptomatic Meckel diverticulum and whether or not to resect an accidentally discovered. Treatment of symptomatic MD is definitive surgery, including diverticulectomy, wedge, and segmental resection. Laparoscopic diagnosis and treatment are possible today.